COVID-19: Implications on Small and Medium Enterprises (SMEs) in Japan - Abdullah, Alias; Seng, Wee Bee; Mohd Huda, Mohd Ikbal; Musa, Noor Azlina (WILAYAH: The International Journal of East Asian Studies, 2021)
The Coronavirus (Covid-19) outbreak has affected all business sectors. The state of emergency, limited movement order and social distancing are amongst the preemptive efforts of the Japanese government to safeguard public health. While recognizing the importance of preventing the immense spread of the virus, there are certain unexplored impacts of the movement control measure on the SMEs in Japan. The objective is to scrutinize the repercussions of the Covid-19 on SMEs in Japan. The study applies a qualitative approach through the analysis of the secondary data from the internet, as well as from the Japanese official government and business association. this article intends to scrutinize the actual implications of the Japanese’s state of emergency on SMEs businesses and to identify the survival strategies of the business. Thus, this study differs from other methods such as other quick online surveys that commonly conducted by market surveys. Our findings contribute towards the actual challenges faced by the SMEs during the pandemic crisis.